Zeltnera fonsecae (Gentianaceae, Chironieae, Chironiinae), a new gypsophilous species endemic from Oaxaca, Mexico - Sandoval-Gutiérrez, Daniel; Vigosa-Mercado, J. Luis; Morales-García, E. Darinka (Phytotaxa, 2024)
During a recent study of the gypsicolous flora of the municipality of San Juan Teita, Oaxaca, a new species of Zeltnera was identified. We revised several herbarium collections, protologues and types, and we concluded that this does not belong to any of the previously described species. In this work, Zeltnera fonsecae, the only Mexican strictly gypsophilous species of the genus, is described and illustrated. Similarities with other species of the genus are commented, a preliminary conservation assessment is proposed, and a key to the species of the genus in Mexico provided. The new species is distinguished from other similar species of Zeltnera by the small size of the plants, cauline and divergent leaves, as well as pentamerous and white flowers. According to the criteria of the IUCN, the category of Vulnerable (VU, D2) is proposed.